Using urinary leucocyte esterase tests as an indicator of infection with gonorrhoea or chlamydia in asymptomatic males in a primary health care setting. (February 2014) - Rahman, Md Saifur; Beever, Warwick; Skov, Steven; Boffa, John
To evaluate a leucocyte esterase test as a predictor of gonorrhoea or chlamydia in asymptomatic Aboriginal males at the Central Australian Aboriginal Congress Male Clinic (Ingkintja), first-void urine samples and clinical information were collected from consecutive asymptomatic males presenting to the Ingkintja in Alice Springs between March 2008 and December 2009. Urine was tested immediately with a leucocyte esterase test dipstick and then by polymerase chain reaction for gonorrhoea and chlamydia. Among the 292 specimens from asymptomatic males, 15.4% were positive for gonorrhoea or chlamydia. In this group, compared with polymerase chain reaction result for gonorrhoea or chlamydia, leucocyte esterase test alone and in combination with age ≤35 years showed sensitivities of 66.7% and 60%, specificities of 90.7% and 94.7%, positive predictive values of 56.6% and 67.5%, negative predictive values of 93.7% and 92.8% and the area under receiver operating characteristics curve values of 0.79 and 0.85, respectively. Leucocyte esterase tests can reasonably be used as a basis for immediate empirical treatment for gonorrhoea or chlamydia in asymptomatic central Australian Aboriginal men under 35 years of age.